2011
DOI: 10.1111/j.1539-6924.2011.01695.x
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Distance of Climate Change

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk 1 Author Posting. © The Authors 2012. This is the author's version of the work. For full bibliographic citation, please refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
895
1
26

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,072 publications
(978 citation statements)
references
References 48 publications
56
895
1
26
Order By: Relevance
“…It seems plausible that temporal framing might help encourage environmentally sustainable travel choices among tourists who are less prone to considering the long-term consequences of their present behaviours. This view is also in line with findings from Spence et al (2012), who investigated public perceptions of climate change. They found that global climate change is largely perceived as a temporally (and geographically) distant threat, and that reduced perceived temporal (and geographic) distance is associated with a stronger preparedness to reduce energy use in response to climate concerns.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It seems plausible that temporal framing might help encourage environmentally sustainable travel choices among tourists who are less prone to considering the long-term consequences of their present behaviours. This view is also in line with findings from Spence et al (2012), who investigated public perceptions of climate change. They found that global climate change is largely perceived as a temporally (and geographically) distant threat, and that reduced perceived temporal (and geographic) distance is associated with a stronger preparedness to reduce energy use in response to climate concerns.…”
Section: Discussionsupporting
confidence: 75%
“…Research shows that environmental problems are often perceived as remote rather than as immediate threats (e.g. Gifford et al, 2009;Spence, Poortinga, & Pidgeon, 2012), which could be the reason behind why the strength of stated behavioural intentions was more sensitive to individual differences in CFC-Future than in CFC-Immediate.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of low carbon technology changes (such as the proposed shift towards low emission vehicles) and societal change towards lower carbon behaviours (such as the increased use of public transport and car-sharing) will only be realised if they are socially acceptable (Christmas et al, 2009), yet research to understand the likelihood of extensive behaviour change towards low carbon demand-side policy options is still in its infancy (Darnton, 2008). Given the scale of societal change that is predicted to be required to reduce emissions, an understanding of public preferences for different low carbon energy and transport policies is essential (Spence et al, 2012). More recent work is indicating that increased public participation is crucial as public preferences are potentially based on complex, and far from transparent, sets of underlying values (Parkhill et al, 2013).…”
Section: Background To Decc's 2050 Calculator and Online Simulationmentioning
confidence: 99%
“…While we are able to identify the importance of such motives in our experiment, it remains to be investigated how strong these motives are in the real world. For instance, in our experiment, the chickpeas are visible and have a direct effect on the number of sliders that can be placed, whereas many environmental externalities, such as greenhouse gas emissions, have effects that occur in the far future and are subject to some degree of uncertainty, hence making them 'psychologically distant' (Spence et al 2012). We did, however, find evidence of a link between the choices in our experiment and the participants' attitudes regarding how to fight climate change, as elicited by the postexperimental questionnaire.…”
Section: Resultsmentioning
confidence: 99%